„Zagęszczenia wieloznaczeń” – gry językowe w poezji Urszuli Kozioł - Sławek , Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article presents the linguistic mechanisms used by the poet Urszula Kozioł to play poetic linguistic games with her readers. Based on selected poems, the article discusses the ways of employing means from various levels of the language system, including the phonetic, morphological, inflection, syntactic and semantic systems. It is pointed out that U. Kozioł’s linguistic games are often based on complex etymological and word-building mechanisms. As a result of these, the poetry is full of unexpected, often ambiguous word forms that surprise the readers with their unconstricted morphological and phonetic form with frequently unspecified and unclear meaning, making room for new, often non-standard interpretations.